Temperatures Surface Mapping of Wurung Crater Area, Bondowoso Regency, East Java In Determination Geothermal Manifestations - Endah Juniarti; Sukir Maryanto; Adi Susilo (Natural B, Journal of Health and Environmental Sciences, 2017)
A research using remote sensing have been done on Kawah Wurung-Ijen. This research was conducted to analyze the distribution of land surface temperature and to identify the geothermal manifestations. The land surface temperature was obtained by using emissivity method of calculating the Normalized Difference Vegetation Index (NDVI). Remote sensing data was used more secund data from Landsat 8. The result shows that the research area has the land surface temperature distribution in ranges 10°C to 50°C. The interpretation shows any anomalous area in ranges 31°C to 50°C that indicated as geothermal potential area. The anomalous are associated with volcanic areas. In the West is associated with Mt. Genteng, in the North is associated with Mt. Gending Waluh. In addition, there is also an anomaly in the East precisely around kolovium of Mt. Kukusan.